Distribution and Functionality of Copy Number Variation across European Cattle Populations - Upadhyay, Maulik; da Silva, Vinicus H.; Megens, Hendrik-Jan; Visker, Marleen H. P. W.; Ajmone-Marsan, Paolo; Bâlteanu, Valentin A.; Dunner, Susana; Garcia, Jose F.; Ginja, Catarina; Kantanen, Juha; Groenen, Martien A. M.; Crooijmans, Richard P. M. A. (Frontiers in Genetics, 2017)
Copy number variation (CNV), which is characterized by large-scale losses or gains of DNA fragments, contributes significantly to genetic and phenotypic variation. Assessing CNV across different European cattle populations might reveal genetic changes responsible for phenotypic differences, which have accumulated throughout the domestication history of cattle as consequences of evolutionary forces that act upon them. To explore pattern of CNVs across European cattle, we genotyped 149 individuals, that represent different European regions, using the Illumina Bovine HD Genotyping array. A total of 9,944 autosomal CNVs were identified in 149 samples using a Hidden Markov Model (HMM) as employed in PennCNV. Animals originating from several breeds of British Isles, and Balkan and Italian regions, on average, displayed higher abundance of CNV counts than Dutch or Alpine animals. A total of 923 CNV regions (CNVRs) were identified by aggregating CNVs overlapping in at least two animals. The hierarchical clustering of CNVRs indicated low differentiation and sharing of high-frequency CNVRs between European cattle populations. Various CNVRs identified in the present study overlapped with olfactory receptor genes and genes related to immune system. In addition, we also detected a CNV overlapping the Kit gene in English longhorn cattle which has previously been associated with colour-sidedness. To conclude, we provide a comprehensive overview of CNV distribution in genome of European cattle. Our results indicate an important role of purifying selection and genomic drift in shaping CNV diversity that exists between different European cattle populations.